Predicting Outcomes in Posterior Lumbar Interbody Fusion Surgery Using the Kaplan-Feinstein Comorbidity Index (Bangladesh Journal of Neurosurgery, 2026)
Objective: This study evaluates the predictive value of the Kaplan-Feinstein Comorbidity  Index (KFI) in determining outcomes of posterior lumbar interbody fusion (PLIF) surgery.  Methods: A retrospective analysis was conducted on 68 patients who underwent PLIF  surgery performed by a single surgeon at a private hospital between 2022 and 2024. The  male-to-female ratio was 3:2, with a minimum follow-up of one year. The KFI was applied  to assess comorbidity burden.  Results: Higher KFI scores correlated with poorer postoperative outcomes. Diabetes  mellitus and ischemic heart disease emerged as significant predictors of adverse surgical  outcomes.  Conclusion: The KFI is a valuable tool for risk stratification in PLIF surgery. Patients with  diabetes and ischemic heart disease may require closer perioperative management to  optimize outcomes. Bang. J Neurosurgery 2025; 14(2):  85-89